ChemInform Abstract: Synthesis of 1, 2, 4‐Triazepine and 1, 2, 5‐Triazocine Derivatives from the Reaction of 2‐Aminobenzohydrazide with π‐Acceptors. Issue 6 (20th February 2013) - El‐Shaieb, Kamal M.; Ameen, Mohamed A.; Abdel‐Latif, Fathy F.; Mohamed, Asmaa H.
Abstract A convenient, one‐pot method for the preparation of 1, 2, 4‐triazepine and 1, 2, 5‐triazocine derivatives is described.